2015
DOI: 10.1302/0301-620x.97b1.34670
|View full text |Cite
|
Sign up to set email alerts
|

Independent validation of the Nottingham Hip Fracture Score and identification of regional variation in patient risk within England

Abstract: The Nottingham Hip Fracture Score (NHFS) was developed to assess the risk of death following a fracture of the hip, based on pre-operative patient characteristics. We performed an independent validation of the NHFS, assessed the degree of geographical variation that exists between different units within the United Kingdom and attempted to define a NHFS level that is associated with high risk of mortality. The NHFS was calculated retrospectively for consecutive patients presenting with a fracture of the hip to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 19 publications
3
31
0
1
Order By: Relevance
“…The NHFS is essentially a weighted seven factor frailty score specific to hip fracture: Age; Cognitive function on admission (Abbreviated Mental Test Score [20] <7); not living at home; sex (male); haemoglobin < 100 g L -1 ; previous malignancy; >1 comorbidity (stroke/transient ischaemic attack; cardiovascular disease; diabetes; previously diagnosed renal disease. It has previously been shown to predict 30-day post hip fracture mortality in the UK [21, 22] and internationally [23]. …”
Section: Methodsmentioning
confidence: 99%
“…The NHFS is essentially a weighted seven factor frailty score specific to hip fracture: Age; Cognitive function on admission (Abbreviated Mental Test Score [20] <7); not living at home; sex (male); haemoglobin < 100 g L -1 ; previous malignancy; >1 comorbidity (stroke/transient ischaemic attack; cardiovascular disease; diabetes; previously diagnosed renal disease. It has previously been shown to predict 30-day post hip fracture mortality in the UK [21, 22] and internationally [23]. …”
Section: Methodsmentioning
confidence: 99%
“…In those studies, the prevalences of highrisk patients were 92% [53], 86% [54], 73% [18], and 45% [71], and an average value of 74% was used, with the range of 45% to 92% used in the sensitivity analysis.…”
Section: Risk Stratificationmentioning
confidence: 99%
“…Highquality economic studies have evaluated the benefits of directing resources toward the focused goal of reducing time to the operating room [19] and the benefits of early initiation of osteoporosis treatment [31,32,35]. Additionally, numerous studies have identified important predictors of perioperative complications, costs, and mortality [5,13,18,41,46,49,53,54,65], suggesting that different patient populations may have different predisposing risk factors, and thus experience different degrees of benefit from a comanagement system. Although the financial issues associated with comanagement programs have been explored [14,19,37], to our knowledge no formal economic analysis based on decision analysis principles-which can be used to synthesize results over multiple studies and create generalizable conclusions-has been performed.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, comorbidities, poor health status, and postoperative complications have been reported as the main mortality predictors in patients with hip fractures. (1,(5)(6)(7)(8)(9)(10)(11) Furthermore, several risk prediction models, such as the Charlson Comorbidity Index (CCI), (12,13) the Orthopedic version of the Physiologic and Operative Severity Score for the Enumeration of Mortality and Morbidity (O-POSSUM), (14,15) and the Nottingham Hip Fracture Score (NHFS), (16,17) have been developed. However, using these models is time consuming because they require special rating scales and further calculations; therefore, they are not yet widely used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%